A Hoplological and Interdisciplinary Perspective on the Lechitic Roots of Today's Poles and Poland - Cynarski, Wojciech J. (Global Journal of Cultural Studies, 2025)
Problem: There are ongoing disputes over the origins of Western Slavs and Poles. The author attempts to describe the state of knowledge in light of recent research and analyzes the content of the new scientific monograph ”About military and physical culture in the lands of Lechia.” He does so with an emphasis on the heritage of military culture. Method: The results of archaeogenetic and hoplological research, as well as an analysis of the relevant literature, are considered together. Logical arguments are used. Results: An approach synthesizing the current state of knowledge, presented in the monograph, is described. This particularly falsifies the hypothesis of the late arrival of the Slavs in Central Europe. The analysis of the author's monograph is supplemented with new observations regarding weapons and other attributes of legendary heroes and demigods. Conclusions: The monograph provides a series of logical proofs of the presence of Slavs, known for example as the Veneti, in Polish lands since at least 2000 BCE, which refutes the hypotheses of a late arrival of Slavs in the Lechitic lands. Genetic studies have demonstrated the continuity of settlement of these lands by the direct ancestors of today's Poles. Similarities have been observed in weaponry and military culture.